2018
DOI: 10.1093/sleep/zsy032
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia—perchance a dream? Results from a NREM/REM sleep awakening study in good sleepers and patients with insomnia

Abstract: This study presents direct evidence that the subjective experience of insomnia might be specifically coupled to the REM sleep state. Assuming chronic hyperarousal as a central pathophysiologically relevant pathway for insomnia, this might become especially evident during REM sleep, thus reflecting a hybrid sleep state in insomnia being coupled with altered sleep perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 65 publications
5
86
1
Order By: Relevance
“…Notably, sleep physiology research shows that insomniacs have fragmented REM sleep (Feige et al., , ; Riemann et al., ), and a recent study showed that a pre‐sleep negative affect induction task increased the number of awakenings during REM sleep (Vandekerckhove & Cluydts, ). Subjective reports are consistent with these sleep physiology findings, such that insomniacs report REM sleep mentation as more wake‐like and emotionally negative than good sleepers (Feige et al., ). Riemann's team presented these findings in the context of highlighting REM instability (i.e.…”
Section: The Neurobiology Of Sleep Reactivitymentioning
confidence: 64%
“…Notably, sleep physiology research shows that insomniacs have fragmented REM sleep (Feige et al., , ; Riemann et al., ), and a recent study showed that a pre‐sleep negative affect induction task increased the number of awakenings during REM sleep (Vandekerckhove & Cluydts, ). Subjective reports are consistent with these sleep physiology findings, such that insomniacs report REM sleep mentation as more wake‐like and emotionally negative than good sleepers (Feige et al., ). Riemann's team presented these findings in the context of highlighting REM instability (i.e.…”
Section: The Neurobiology Of Sleep Reactivitymentioning
confidence: 64%
“…Cell body-specific striatal lesions of the rostral striatum induce profound sleep fragmentation, which is highly characteristic of insomnia 45,49 . As discussed more extensively in the Supplementary Note, fragmented REM sleep is highly characteristic of insomnia and related to the ongoing thought-like mental content that makes patients with insomnia underestimate sleep duration [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…EEG microstate analysis may serve as a valuable paradigm for future investigations on nocturnal mentation in ID. Previous studies have shown that insomnia severity is associated with the frequency of thought-like nocturnal mentation ( 57 ) which might be experienced as wakefulness ( 58 ). It is still unclear, however, whether (and how) distinct nocturnal thought content contributes differentially to the experience of insomnia ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%